2003
DOI: 10.1046/j.1440-1819.2003.01115.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances and depression in the elderly in Japan

Abstract: The purpose of the present study was to evaluate the relationship between sleep disturbances and depression in the Japanese elderly. Methods: These investigations in the Japanese elderly were carried out with the Geriatric Depression Scale, the Pittsburgh Sleep Quality Index, and questions on restless legs syndrome and nocturnal eating disorder. A total of 2023 people (male: 1008; female: 1015; average age: 74.2 ± 6.3 years) were analyzed by c 2 test and simple and multiple logistic regression. The prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
2
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 20 publications
4
40
2
2
Order By: Relevance
“…Previous studies have also suggested its association with mental health problems, such as anxiety disorder and major depressive disorder (Ohayon, 2004). In studies of elderly Japanese, sleep mental health in korea and japandisturbances were found to be significantly associated with depression (Sukegawa et al, 2003;Sugahara et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have also suggested its association with mental health problems, such as anxiety disorder and major depressive disorder (Ohayon, 2004). In studies of elderly Japanese, sleep mental health in korea and japandisturbances were found to be significantly associated with depression (Sukegawa et al, 2003;Sugahara et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
“…In 2 studies, 16,54 an increased risk of depression was observed only in male patients; female patients did not show an elevated depression risk ( 16 In a study of elderly Japanese patients, RLS was associated with depression in men aged 65-74 years. 54 However, no associations were observed among men aged ≥ 75 years or among women in either age group. Other studies, however, have shown stronger associations between depression and RLS in women (Table 1).…”
Section: Figure 1 Odds Ratios For the Associations Between Restless mentioning
confidence: 99%
“…More then 90% of patients with RLS have sleep disorders (3). On the other hand, epidemiologic data suggest higher prevalence of depression among patients with RLS (4)(5)(6)(7)(8). There is a strong relationship between insomnia and depression, as insomnia is a symptom of depression and also a risk factor to deteriorate depression (9).…”
Section: Introductionmentioning
confidence: 99%